The Future of Social Policy in Europe - Ayşe İdil Aybars (Ankara Avrupa Çalışmaları Dergisi)
Social policy in the European Union (EU) remains sidelined in the debates on the future of Europe. In the last decade, EU has faced numerous crises having significant repercussions for its social policies, including immigration waves, the Brexit and the Covid-19 pandemic. As an area of direct concern to EU citizens, with its features on employment, education/training, non-discrimination and equality bearing crucial implications for their daily lives, social policy should be re-considered from an angle that encompasses the citizens’ perspective and effectively addresses the major challenges it faces in the new global order. The main objective of this study is to explore the implications of these challenges for EU social policy, which in turn, has a key role in shaping the future of the EU.